Let's break down the steps for solving the given equation to determine which statement is true.
Initially, we have:
\[ 3x - 9x + 1 = 2(-3x + 1) - 1 \]
Simplifying the left side:
\[ 3x - 9x + 1 = -6x + 1 \]
Now simplifying the right side:
\[ 2(-3x + 1) - 1 = -6x + 2 - 1 = -6x + 1 \]
So now we have:
\[ -6x + 1 = -6x + 1 \]
Since both sides of the equation are identical, this indicates that any value of \( x \) will satisfy the equation. Therefore, the equation has infinitely many solutions.
So the correct statement is:
There are infinitely many solutions to the equation.